Simultaneous Determination of Ciprofloxacin Hydrochloride and Dexamethasone Sodium Phosphate in Eye Drops by HPLC - Prakash Katakam; Karanam R. Sireesha (E-Journal of Chemistry)
A liquid chromatographic method was developed and validated for the simultaneous determination of ciprofloxacin hydrochloride and dexamethasone sodium phosphate in bulk and pharmaceutical formulations. Optimum separation was achieved in less than 5 min using a C18 column (250 mmx4.6 mm i.d, 5μ particle size) by isocratic elution. The mobile phase consisting of a mixture of mixed phosphate buffer (pH 4) and acetonitrile (65:35, v/v) was used. Column effluents were monitored at 254 nm at a flow rate of 1ml/min. Retention times of ciprofloxacin hydrochloride and dexamethasone sodium phosphate were 2.0 and 3.16 min respectively. The linearity of ciprofloxacin hydrochloride and dexamethasone sodium phosphate was in the range of 3-18 μg/ml and 1-6 μg/ml respectively. Developed method was economical in terms of the time taken and amount of solvent consumed for each analysis. The method was validated and successfully applied to the simultaneous determination of ciprofloxacin hydrochloride and dexamethasone sodium phosphate in bulk and pharmaceutical formulations.